IMPLEMENTASI SISTEM PENTANAHAN GRID PADA TOWER TRANSMISI 150 KV (APLIKASI PADA TOWER SUTT 150 KV TOWER 33) - Darmana, Ija Darma (LLDIKTI Wilayah X, 2015)
Grounding system is one form of the integrated system in the electricity system for the security of the overall system of interference that allows the damage to the equipment, resulting in breaking the continuity of power service to consumers. Some ways earthing system used is by planting electrodes (conductors) in soil vertically (rod), horizontal (parallel to the ground) in the form of a grid (grid) and the combination of both the arrangement in order to obtain an effective earthing configuration of the electrodes used. The experiment was conducted at the tower no. 33 (Tarantang) Pegambiran Padang. Earthing measurement tower is done by measuring the resistance value through a tower grounding foot tower by using earth tester. Skeletons tower connected to the grounding grid plus with one electrode rod. From the research that has been carried out, with an additional earthing system is able to reduce the value of the grounding grid to 0.5 Î©. The smaller the value grounding in the can, the better the system grounding. To get the value of grounding that less than 1 Ohm, grounding by adding a grounding grid into the right solution. Keywords: System Grounding Grid.